ANALISIS ARUS PURBA PADA DAERAH KEDUNGWRINGIN, KECAMATAN SEMPOR, JAWA TENGAH: PALEOCURRENT ANALYSIS OF KEDUNGWRINGIN REGION, SEMPOR DISTRICT, CENTRAL JAVA - Aditya Henri Saputra; Budi Wijaya; Rendy (Journal of Geoscience Engineering & Energy (JOGEE), 2022)
The exposed sandstone unit in the research area located in the Kedungwringin area, Sempor District, Central Java Province is included in the Waturanda Formation. At the research location, there are 4 exposed rock units, namely Tuff Unit, Sandstone Unit, Breccia Unit, and Alluvial Unit. The sandstone unit in the study area has a type of Arkosic Wacke Sandstone. Measurable stratigraphic measurements were carried out on the three tracks and it was found that the research area was stratigraphically in the sandstone unit and the breccia unit in the south of the study area, and had a southwest-southeast current direction which was obtained based on measurements of sedimentary structures that developed in the study area.